2020
DOI: 10.1002/slct.202002158
|View full text |Cite
|
Sign up to set email alerts
|

CTAB‐PLGA Curcumin Nanoparticles: Preparation, Biophysical Characterization and Their Enhanced Antifungal Activity against Phytopathogenic Fungus Pythium ultimum

Abstract: In the current study, we utilized application of nanotechnological advancements to synthesize positively charged curcumin nanoparticles (CurNPs). In CurNPs, curcumin (Cur) was encapsulated by a stabilizer, polymer poly(lactic‐co‐glycolic acid) (PLGA) and its surface charge was modified by cationic surfactant cethyltrimetylammonium bromide (CTAB). Characterization methods involving UV‐visible spectroscopy, X‐ray diffraction (XRD), transmission electron microscopy (TEM) and dynamic light scattering (DLS) were em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Because they are linked to the clicking present in the cell membrane and lead to the release of synthesized silver nanoparticles at 0.02 mmol/ml. Journal of Nanomaterials silver ions that work to improve the permeability of the cell membrane, nanoparticles with a high surface area allow them to have the best contact and interaction with the microbial cell [28]. Another suggested mechanism that explain the impact of AgNPs in cell wall is the thickness and composition of cell wall and the peptidogly content can along with the charged of lipopolysaccharide [22].…”
Section: Resultsmentioning
confidence: 99%
“…Because they are linked to the clicking present in the cell membrane and lead to the release of synthesized silver nanoparticles at 0.02 mmol/ml. Journal of Nanomaterials silver ions that work to improve the permeability of the cell membrane, nanoparticles with a high surface area allow them to have the best contact and interaction with the microbial cell [28]. Another suggested mechanism that explain the impact of AgNPs in cell wall is the thickness and composition of cell wall and the peptidogly content can along with the charged of lipopolysaccharide [22].…”
Section: Resultsmentioning
confidence: 99%
“…Researchers like McDonnell and Russell have shown that nanoparticles interact with phosphorus or sulfur, making proteins containing, such as DNA, ideal binding sites for nanoparticles [ 77 ]. The size and surface area of silver nanoparticles enable them to connect with cell DNA, facilitating interaction with microbial cell membranes and the release of silver ions, which enhance membrane permeability [ 78 , 79 ]. Factors such as cell wall thickness, composition, peptidoglycan concentration, and lipopolysaccharide charge contribute to how AgNPs affect cell walls [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that Cur has a very high potential to treat infections caused by various viruses, including SARS‐CoV‐2, the human immunodeficiency virus (HIV), dengue virus, herpes simplex virus (HSV), hepatitis virus, influenza A virus (IAV), Ebola virus, mosquito‐borne viruses (the Zika virus and Chikungunya virus), Japanese Encephalitis virus (JEV), Feline infectious peritonitis virus (FIPV), vesicular stomatitis virus (VSV), flock house virus (FHV), Human enterovirus71 (EV71), human cytomegalovirus (HCMV), Epstein–Barr virus (EBV), bovine herpesvirus 1 (BHV 1), rift valley fever virus (RVFV), human norovirus (HuNoV), respiratory syncytial virus (RSV), fish viral hemorrhagic septicemia virus (VHSV), and so on (Lo et al, 2021; Mathew & Hsu, 2018; Rai et al, 2020; Shanmugarajan, Prabitha, Kumar, & Suresh, 2020). Also, antifungal (Khatua et al, 2020), antiparasitic (Gutiérrez‐Gutiérrez et al, 2020), antibacterial (Perera et al, 2020), antioxidant (Abu‐Taweel et al, 2020), anticancer (Sebastiammal et al, 2020), antiinflammation (Pontes‐Quero, Benito‐Garzón, Cano, Aguilar, & Vázquez‐Lasa, 2021), antidiabetic (Shamsi‐Goushki et al, 2020) activities, and so on are other reported biological activities of Cur (Afshar et al, 2021; Alotaibi, Tousson, El‐Masry, Altwaijry, & Saleh, 2021; Ban et al, 2020; Basit et al, 2020; He et al, 2021; Kang, Jung, Hyeon, Seon, & Lee, 2020; Zhang et al, 2020). Nevertheless, a comprehensive review of some literature on the clinical pharmacology of herbal demonstrated that a variety of natural and botanical ingredients have a higher risk of adverse reactions.…”
Section: Introductionmentioning
confidence: 99%